Efficient bioreduction of 4-phenyl-2-butanone to drug precursor (S)-4-phenyl-2-butanol by a whole-cell biocatalyst using a novel hybrid design technique - Bayhan, Beyzanur; Ozdemir, Akin; Dertli, Enes; Sahin, Engin (ELSEVIER, 2024)
Asymmetric synthesis is a critical tactic in pharmaceutical industries for creating chiral medications as it allows an enantiomer to be obtained in synthetic chemistry. The asymmetric bioreduction processes by biocatalysts have shown significant potential in producing chiral alcohols. The amount of substrate and the production method of the biocatalytic synthesis of (S)-4-phenyl-2-butanol ((S)-2) are not still desired levels. Furthermore, the biocatalytic asymmetric reduction of 4-phenyl-2-butanone (1) to (R)- or (S)-4-phenyl-2-butanol did not use any mathematical modeling techniques. In this study, the asymmetric bioreduction of 1 was carried out in this work employing Lactobacillus paracasei BD71 biocatalyst and a novel hybrid design-based optimization approach. By using the hybrid design technique, the optimal circumstances were discovered to be pH = 7, temperature = 29 degrees C, incubation period = 66 h, and agitation speed = 189 rpm. Also, the enantiomeric excess (ee) and conversion could be 99.15 % and 98.19 %, respectively. Next, (S)-2 was acquired to be ee: 99 %, conversion: >99 %, and yield: 97 % from the optimum bioreduction conditions. Furthermore, 14.08 g of 1 under optimal conditions was entirely transformed into (S)-2 (13.84 g, 97 % isolated yield). This study is the first research attempt to use a biocatalyst and an innovative and new hybrid design-based optimization approach to fabricate enantiopure (S)-2 at a high gram scale. This work has successfully demonstrated that the new hybrid design-based optimization technique is applicable to biocatalytic asymmetric reduction processes.
Keywords: Biocatalysts; Asymmetric bioreduction; Drug precursor; Green chemistry; ( s)-4-phenyl-2-butanol; ASYMMETRIC REDUCTION; ALCOHOL-DEHYDROGENASE; KETONES; PLANT; Chemistry